Prevalence and molecular characterization of Cryptosporidium spp. and Giardia duodenalis in dairy cattle in Gansu, northwest China - Wang Yilin; Cao Jianke; Chang Yankai; Yu Fuchang; Zhang Sumei; Wang Rongjun; Zhang Longxian (Parasite, 2020)
Cryptosporidium spp. and Giardia duodenalis are common gastrointestinal parasites with a broad range of hosts, including humans, livestock, and wildlife. To examine the infection status and assess the zoonotic potential of Cryptosporidium spp. and G. duodenalis in dairy cattle in Gansu, China, a total of 1414 fecal samples were collected from the rectum, with one sample collected from each individual animal. All the samples were tested using nested PCR based on the small subunit ribosomal RNA (SSU rRNA) gene of Cryptosporidium spp. and G. duodenalis. The overall infection rates of Cryptosporidium spp. and Giardia duodenalis were 4.2% (n = 59) and 1.0% (n = 14), respectively. Four Cryptosporidium species were identified: C. andersoni (n = 42), C. parvum (n = 12), C. bovis (n = 5), and C. ryanae (n = 1). In further analyses of subtypes of C. parvum isolates based on the 60 kDa glycoprotein (gp60) gene, five were successfully subtyped as IIdA19G1 (n = 4) and IIdA15G1 (n = 1). All 14 G. duodenalis isolates were identified as assemblage E using the triosephosphate isomerase (tpi) gene. The relatively low positive rates of Cryptosporidium spp. and G. duodenalis detected here and the predominance of non-human pathogenic species/assemblages of these parasites indicated their unique transmission dynamics in this area and the low level of threat posed to public health. However, continuous monitoring and further studies of these parasites should be conducted for the prevention and control of these pathogens.